Supervision of The Head of The Room Related To Compliance Nurse In Preventing Pressure Instructions At Fatmawati RSUP In South Jakarta - Khairul Nasri; Enie Novieastari (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
Background: Supervision is part of directive function of a manager. Supervision is carried out to ensure nurses work according to standard. Actually, the quality service in hospital can be improved with supervision. Objective: to determine the relationship between the supervision of the head of the room in the compliance of nurses in preventing pressure injuries. Design: this study was a quantitative study with a cross-sectional design approach to determine the relationship between the independent variable and the dependent variable. Data obtained through the google form application. The instrument used was made by the researchers themselves with modifications from sources based on the theoretical basis of Nursalam’s supervision. Questionnaire A demographic data, questionnaire B implementation of supervision, questionnaire C compliance of nurses. The analysis in this study included univariate and bivariate analysis. This study used the Spearman Rank, Mann-Whitney, Kruskal-Wallis test. Results: Nurses aged 24-53 years, Working period 1-32 years. Female gender 87,7 %, D3 Nursing education 59,2 %, Competency level PK II 36,2 %, Never attended 54,6 %, Marred 80% and employment status as ASN 53,1%. Conclusion: There were three dimensions of supervision that affect compliance, namely supervision techniques, supervision principles and supervision models. There was correlation between supervision and nurse compliance which was quite strong, significant and unidirectional, expect that the dimension of supervision routine activities had a very weak correlation. All characteristic variables had no correlation with adherence except for age, which had a very weak relationship. There was a weak, significant and unidirectional correlation between composite supervision and the implementation of nurse compliance. The results of the analysis of nurse compliance in preventing pressure injuries were 80%. Recommendation: It is necessary to know other factors besides supervision that affect compliance. Suggestion for further researchers is research with a qualitative approach.